2008
DOI: 10.1053/j.gastro.2008.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus-Related Microbial Translocation and Progression of Hepatitis C

Abstract: Background & Aims-HIV-1 infection has been associated with enhanced microbial translocation, and microbial translocation is a mechanism through which alcohol and some enteric conditions cause liver disease. We hypothesized that HIV promotes liver disease by enhancing microbial translocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
207
3
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(238 citation statements)
references
References 43 publications
17
207
3
11
Order By: Relevance
“…Balagopal et al demonstrated that in HIV-infected individuals, measures of microbial translocation are strongly associated with markers of hepatitis C virus (HCV)-related liver disease progression (e.g., cirrhosis) (123). Similarly, for 98 HIV/HCV coinfected patients on virologically suppressive ART, we reported increased sCD14 levels in subjects either harboring aggressive HCV genotypes (i.e., genotypes 1 to 4) or presenting with cirrhosis (129).…”
Section: Microbial Translocation In Liver Diseasesupporting
confidence: 66%
See 1 more Smart Citation
“…Balagopal et al demonstrated that in HIV-infected individuals, measures of microbial translocation are strongly associated with markers of hepatitis C virus (HCV)-related liver disease progression (e.g., cirrhosis) (123). Similarly, for 98 HIV/HCV coinfected patients on virologically suppressive ART, we reported increased sCD14 levels in subjects either harboring aggressive HCV genotypes (i.e., genotypes 1 to 4) or presenting with cirrhosis (129).…”
Section: Microbial Translocation In Liver Diseasesupporting
confidence: 66%
“…Indeed, LPS has been shown to accelerate liver fibrosis through TLR-4 signaling on Kupffer cells following membrane binding via LPS binding protein (LBP) and CD14 (121). These events lead to the generation of superoxide and the release of proinflammatory and profibrogenic cytokines such as TNF-␣, IL-1, IL-6, and IL-12, all of which induce liver damage (122,123). Consistent with these findings, microbial translocation has been shown to contribute to liver disease in several clinical settings, such as alcoholic liver disease (124,125) and other enteric processes (126)(127)(128).…”
Section: Microbial Translocation In Liver Diseasementioning
confidence: 99%
“…Whereas the hallmark of primary HIV infection is a substantial CD4 ϩ T cell loss at mucosal sites and elsewhere (20), chronic HIV infection is characterized by the inability of the immune system to control viral replication (22) as well as by a state of chronic immune activation. Mucosal translocation of microbial bioactive substances such as lipopolysaccharides (LPS) may be an important stimulus of this chronic immune activation (4,5,9,11,14,20,29,40,42,49). In fact, markers of chronic activation, such as CD38 on CD8 ϩ T cells, appear to be better suited to predicting clinical progression in HIV infection than HIV RNA levels and CD4 ϩ T cell counts (18,24,26,28,46).…”
mentioning
confidence: 99%
“…Persistent systemic exposure to bacterial antigens from MT triggers immune activation and inflammation in HIVinfected adults (25,26). MT is associated with T-cell activation, which predicts systemic inflammation, mortality, HIV progression, and progression of comorbidities such as cardiovascular disease (25,26,(29)(30)(31).…”
Section: Bacteria and The Gi Tractmentioning
confidence: 99%